Photochromic printing and spectral properties of luminous polyester non-woven fabric. Issue 3 (21st January 2020) - Li, Jing; Li, Yonggui; Song, Xiaolei; Chen, Haizhen
Abstract : Considering the potential application for multicolor luminescent fabrics, a new non-woven fabric capable of emitting blue-violet light was prepared. Luminous non-woven fabrics were prepared using rare-earth strontium aluminate (SrAl2 O4 ) material and polyester (poly(ethylene terephthalate)) through the spun-bonding method. These fabrics were treated with a purple-emitting photosensitive material using the printing and dyeing technique. In the present study, the surface morphologies, absorption spectral properties and photochromic properties of the luminous non-woven fabrics were investigated. The printing paste could obtain certain roughness on the surface of these fabrics. The luminous characteristics of fabrics were changed by the printing process, which have been proved by fluorescence spectrophotometer and PR-650 spectral radiation analyzer. The results revealed that fabrics treated in the process of photochromic printing had two absorption wavelengths of 280 and 365 nm. The results also showed that the optimum doping concentration was 10%, and quenching occurred at excess. The fabrics exhibited good luminous effects and photochromic properties, and the emission wavelength and light color of the fabrics after the modification were blueshifted.